Analisis Tentang Perlindungan Hukum Terhadap Para Pihak Dalam Perjanjian Waralaba Di Indonesia - Wahyuningtiyas, Sari; , Septarina Budiwati, S.H., M.H (2017)
This research aims to know the regulations of the franchise agreement practice in Indonesia as well as to know the legal protection for the franchisor and for the franchisee in the franchise agreement in Indonesia. The method of approach used by the writer is the normative legal approach which was conducted by studying the literature and secondary data. Kind of research used by the writer in this research is a libary research that used primary and secondary data. The method of data collection in this research used the technique of library research which was conducted by finding data in the forms of literature which were necessary and related to this mini thesis. Based on the results of the research and discussion, it can be concluded that the legal protection on the parties in the franchise agreement in Indonesia is embodied in the provision of Kitab Undang-Undang Hukum Perdata (Civil Code), Act Number 15 of 2001 regarding Brand, Act Number 30 of 2000 regarding Trade Secret, and Government Regulation of the Republic of Indonesia Number 42 of 2007 regarding franchise. The existence of the regulations are merely to protect the parties in running the franchise business.